AHNAK KO Mice are Protected from Diet-Induced Obesity but are Glucose Intolerant - Ramdas, M.; Harel, C.; Armoni, M.; Karnieli, E. (Hormone and Metabolic Research, 2015)
AHNAK is a 700 KD phosphoprotein primarily involved in calcium signaling in various cell types and regulating cytoskeletal organization and cell membrane architecture. AHNAK expression has also been associated with obesity. To investigate the role of AHNAK in regulating metabolic homeostasis, we studied whole body AHNAK knockout mice (KO) on either regular chow or high-fat diet (HFD). KO mice had a leaner phenotype and were resistant to high-fat diet-induced obesity (DIO), as reflected by a reduction in adipose tissue mass in conjunction with higher lean mass compared to wild-type controls (WT). However, KO mice exhibited higher fasting glucose levels, impaired glucose tolerance, and diminished serum insulin levels on either diet. Concomitantly, KO mice on HFD displayed defects in insulin signaling, as evident from reduced Akt phosphorylation and decreased cellular glucose transporter (Glut4) levels. Glucose intolerance and insulin resistance were also associated with changes in expression of genes regulating fat, glucose, and energy metabolism in adipose tissue and liver. Taken together, these data demonstrate that (a) AHNAK is involved in glucose homeostasis and weight balance (b) under normal feeding KO mice are insulin sensitive yet insulin deficient; and (c) AHNAK deletion protects against HFD-induced obesity, but not against HFD-induced insulin resistance and glucose intolerance in vivo.
Keywords: obesity; insulin resistance; metabolic syndrome